Adsorção dos herbicidas 2,4-diclorofenoxiacetato de sódio (2,4 - D) e 6-cloro, 4-N-etila-2-N-propan-2-ila-1-1,3,5-triazina-2,4-diamina de sódio (atrazina) em Hidróxidos Duplos Lamelares [Co-Al-Cl] - Calisto, Josiane de Souza (2020)
The herbicides 2,4-dichlorophenoxyacetate sodium (2,4-D) ee 6-chloro, 4-N-ethyl-2-N-propan-2-yl-1-1,3,5-triazine-2,4 - sodium diamine (atrazine) are among the most commercialized active ingredients in the country and with a significant contribution to the production of agricultural commodities. However, the growing concern with the contamination of the environment, especially water bodies, justifies the need to develop technologies for removing contaminants. Therefore, the objective of this work was to evaluate the adsorption efficacy of herbicides (2,4-D and atrazine) by layered double hydroxides (LDH) [Co-Al-Cl]. The experimental study consisted of the synthesis of LDH [Co-Al-Cl] by the method of coprecipitation at constant pH 8.0±0.5, structural characterization of the adsorbent by X-Ray Diffractometry (XRD), morphological characterization by Scanning Electron Microscopy (SEM), determination of the specific surface area by Brunauer-Emmett-Teller (B.E.T.) method. and herbicide adsorption tests. The adsorption tests were carried out in batches from solutions of the two herbicides at pH 5 and under agitation. The kinetic study of adsorption was carried out at room temperature (298 K) and in the thermodynamic study the following temperatures were investigated: 298, 308, 318 and 328 K. With the kinetic data of adsorption, adjustment was made to the linear mathematical models of pseudo -first order and pseudo-second order. For the study of isotherms, adjustments to the mathematical models proposed by Langmuir and Freundlich were used. The XRD result of LDH [Co-Al-Cl] showed defined diffraction peaks, which were indexed to the hexagonal structure, rhombohedral symmetry, spatial group R(-3) m (JCPDS 14-191). The kinetic experimental adsorption data for both 2,4-D and atrazine fit better to the pseudo-second order model, suggesting that the adsorption rate of the pesticides was dependent on the concentration of the pesticide (2,4-D or atrazine) adsorbed on LDH and also its concentration in equilibrium with that which was not adsorbed. The adsorption process for both pesticides was best described by the Freundlich isotherm describing a physical interaction between the adsorbent and the adsorbate with the values of 1/n in the range 0 to 1, suggesting that the adsorption in LDH is favorable and greater than 1, indicating that the adsorbent sites are energetically heterogeneous. The thermodynamic parameters obtained indicated that the adsorption was spontaneous, exothermic and with a decrease in the degree of freedom (disorder) among the species adsorbed on the LDH surface. The 2,4-D adsorption process by LDH showed higher values of adsorptive capacity (27.17 mg g-1 at 308 K) than atrazine (1.69 mg g-1 at 308 K). Therefore, it was concluded that LDH [Co-Al-Cl] can be used as an effective adsorbent in the removal of herbicides, mainly for 2,4-D, in the aquatic environment and thus mitigate pollution by pesticides.